Examination of Depression Levels in Individuals Aged 65 and Over - Rukuye Aylaz; Nuri Yıldırım; Fidan Balkaya (Yaşlı Sorunları Araştırma Dergisi)
Increasing life expectancy and demographic variables such as gender and age may increase the prevalence of depression in the elderly. This study was conducted to examine the depression levels of individuals aged 65 years and older, living in a district of a province in the Eastern Anatolia Region of Turkey. In this descriptive study, sample calculation formula with known universe was utilized. Therefore, the research was conducted with 333 individuals aged 65 and over, residing in a district of Turkey, between July and September 2017. "Personal Information Form" and "Geriatric Depression Scale" were employed to collect study data. Descriptive statistics, independent samples t-test, Kruskal-Wallis, and analysis of variance were utilized in the analysis. Significance level of p<0.05 was adopted. 73,58% of the participants were 65-74 years old, 60,06% were males, 97,28% were married, and 34,90% were housewives. It was found that 68,20% of the participants were depressed and 15,60% were at risk of depression. It was also found that there was a statistically significant difference between the mean scores of the Geriatrics Depression Scale and education, people living with them, source of income, and chronic disease status. In the study, it was found that the mean depression scores of the participants who were illiterate, living alone, living on 65-year-old pension and having more than one chronic disease were higher. When the mean scale score of the participants was evaluated (17,24±6,13), it was revealed that the majority of them were depressed. It is recommended that the individuals with high depression scores be directed to a physician, social support networks should be strengthened, and the elderly should be encouraged to engage in activities appropriate to their capacity.